2019
DOI: 10.26753/jikk.v14i3.350
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Edukasi Breastfeeding Ibu Post Partum Terhadap Breasfeeding Self Efficacy

Abstract: The Baby must receive exclusive breastfeeding at the first six months of development from birth. Exclusive breastfeeding is still bellow of the target. Nutrition is important for baby’s survival, growth, and development. Mother's knowledge about exclusive breastfeeding take effect on exclusive breastfeeding. Knowledge and trust of the mother about breastfeeding can be enhanced by health education. This research to analyze the effect of breastfeeding education onpost-partum mothers regarding breastfeeding self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
5
0
8
Order By: Relevance
“…Riyanti et al's 21 research state a difference between breastfeeding self-efficacy before and after counseling. So it can be concluded that the less counseling, the mother's confidence level will also decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riyanti et al's 21 research state a difference between breastfeeding self-efficacy before and after counseling. So it can be concluded that the less counseling, the mother's confidence level will also decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the importance of counseling related to maternal beliefs earlier in the third trimester so pregnant women will have high confidence to breastfeed. 21,22 Breastfeeding success is the mother's ability to provide exclusive breastfeeding and the correct breastfeeding technique. Proper breastfeeding technique is a factor in breastfeeding success, which needs to be considered in breastfeeding techniques, namely the breastfeeding position and attachment of the baby's mouth to the mother's breast.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian ini sejalan dengan penelitian dari Riyanti et al, (2019) mengenai pengaruh konseling teknik menyusui yang benar terhadap pengetahuan dan sikap pada ibu post partum dengan hasil p-value < 0,005 yang artinya ada pengaruh dari pemberian konseling teknik menyusui yang benar terhadap pengetahuan ibu post partum di wilayah kerja Puskesmas Rujali Ambon.…”
Section: Pembahasanunclassified
“…self-efficacy dapat dimodifikasi dengan memberikan edukasi. Sebuah studi melaporkan bahwa edukasi menyusui secara signifikan berpengaruh terhadap peningkatan self-efficacy ibu menyusui (Riyanti et al, 2019). Studi lain melaporkan bahwa edukasi pada masa prenatal berpengaruh terhadap breastfeeding self-efficacy (Fata & Rahmawati, 2016).…”
Section: Breastfeedingunclassified